The effect of iron supplementation on the speed of cardiac recovery for some young female trainees - Zuheer Hassan, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to identify the effect of iron supplementation on the speed of cardiac recovery for trained women. We have noticed that many of the trained women have cardiac recovery problems and slowed after physical effort to recover the heartbeat, as the relationship between anemia and physical activity has been widely studied. Because anemia also affects female athletes, anemia can lead to physical stress, fatigue, and functional disorders. Given that blood functions are the transport of oxygen, food, and biological compounds to tissues, especially the compound hemoglobin and iron, which play a central role in cardiorespiratory homeostasis, it has been suggested that physical activity in and of itself can be a cause of anemia. It is believed that the combination of insufficient food intake and menstrual losses is the main cause of anemia in women, as well as the fluctuation of hemoglobin concentration in women, especially during and after the menstrual cycle. The experimental method was used for its suitability and the nature of the research, as the research community was deliberately chosen, which numbered (6) trainees, and after presenting the results, analyzing, and discussing them, the researcher concluded that iron compounds contributed and had a positive effect on the speed of cardiac recovery of the trainees.